judul artikel revisi - nama blkg, namadpn (Journal for Social Determinants of Health, 2009)
This chapter investigates measures of journal performance and ranking. It begins by exploring the principal conventional sources of citation data, Web of Science and Scopus, and compares these with alternatives such as Google Scholar. Critical variables in citation analyses include coverage by discipline and different article types, such as review articles compared to articles documenting new research. The chapter concludes with an exploration of alternative metrics.abstrakyuitiu iuyuiyui yiyuuiy yiuyiui uityivf6u iutyui yurtyue t